Avaliação da eficácia de um programa para cessação de tabagismo e controle da fissura - Patricia Maria da Silva Roggi (2014)
Introduction: The smoking or nicotine dependence is a chronic disease whose course is usually marked by attempts to quit, short periods of abstinence and return to the usual pattern of cigarette consumption. The craving is considered a major cause of relapse during abstinence from tobacco and thus its importance is highlighted in smoking cessation. Objective: This study aimed to develop and investigate the impact of an intervention to reduce control craving on abstinence from tobacco. Method: We initially performed a literature review, from which we identified the Cognitive Behavioral Therapy, and psychoeducation, redirection of attention, imagery, relaxation, exposure to response prevention and relapse prevention, the most used techniques for treatment of tobacco dependence. The first study, we compared a group of patients who stopped and not stopped smoking treated with the standard protocol. Their goal was to identify a neuropsychological profile that related to success in the treatment of smoking cessation and predictors of this outcome variables. In the second study, a randomized clinical trial was conducted comparing two groups of smokers who treated with a focused intervention in craving (treatment group) or a placebo protocol (control group), both associated with standard treatment. In this work, the goal was to develop an intervention that would reduce the symptoms of craving related to tobacco abstinence. Results: In the first study, patients who stopped smoking belonged to a higher socioeconomic status, had a degree of dependence on higher nicotine levels and reported more severe craving. Patients who failed to quitting smoking reported higher levels of attentional impulsivity, cognitive flexibility (perseverative responses and errors in the letters Wisconsin) and more symptoms of test anxiety. The dropout group was younger, had less education and higher levels of attentional impulsivity type and not planning impulsivity type. In the second study, we observed significant differences in the average of the subtests and motor impulsivity and sensation seeking (Impulsive 9 Behavior Scale - UPPS) among patients in the control condition, in addition to lower outcomes as learning over trials (LOT) and post-distraction recall trial and higher rates of retroactive interference (ITR) (Test of auditory-verbal Learning Rey). Conclusion: The impulsivity shown to be a factor hampering the engagement in treatment for smoking cessation, and an aspect that is committed to participation and adherence to treatment. The treatment focused on craving promoted greater reduction in symptoms of craving than a control treatment based only on interventions to prevent relapse, although this result did not reach statistical significance. The farmacoterapie appears to have worked as one variable confounding the results, a fact that makes necessary further investigations so that the treatment is applied in groups of patients formed according to the level of nicotine dependence.